Tumour irradiation combined with vascular-targeted photodynamic therapy enhances antitumour effects in pre-clinical prostate cancer - Sjoberg, Hanna T.; Philippou, Yiannis; Magnussen, Anette L.; Tullis, Iain D. C.; Bridges, Esther; Chatrian, Andrea; Lefebvre, Joel; Tam, Ka Ho; Murphy, Emma A.; Rittscher, Jens; Preise, Dina; Agemy, Lilach; et al. (British journal of cancer, 2021)
Background There is a need to improve the treatment of prostate cancer (PCa) and reduce treatment side effects. Vascular-targeted photodynamic therapy (VTP) is a focal therapy for low-risk low-volume localised PCa, which rapidly disrupts targeted tumour vessels. There is interest in expanding the use of VTP to higher-risk disease. Tumour vasculature is characterised by vessel immaturity, increased permeability, aberrant branching and inefficient flow. FRT alters the tumour microenvironment and promotes transient ‘vascular normalisation’. We hypothesised that multimodality therapy combining fractionated radiotherapy (FRT) and VTP could improve PCa tumour control compared against monotherapy with FRT or VTP. Methods We investigated whether sequential delivery of FRT followed by VTP 7 days later improves flank TRAMP-C1 PCa tumour allograft control compared to monotherapy with FRT or VTP. Results FRT induced ‘vascular normalisation’ changes in PCa flank tumour allografts, improving vascular function as demonstrated using dynamic contrast-enhanced magnetic resonance imaging. FRT followed by VTP significantly delayed tumour growth in flank PCa allograft pre-clinical models, compared with monotherapy with FRT or VTP, and improved overall survival. Conclusion Combining FRT and VTP may be a promising multimodal approach in PCa therapy. This provides proof-of-concept for this multimodality treatment to inform early phase clinical trials.